Материалы по биологии исландского песочника на о. Врангеля - Дорогой, И.В. (Вестник зоологии, 1982)
The knot, Callidris canutus L., is a usual nesting bird of the Wrangel island. Under optimal habitat conditions. the nesting density. often exceeds six pairs per I sq. "km. Partners share the brooding,but brood is «conducted» exclusively by male. A complete clutch consists of four eggs. The dipteran larvae play an essential role in the knot's diet. in June.